PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA TOPIK MENGENAL JENIS DAN NILAI NOMINAL UANG SISWA KELAS I SD - Nur Azizah Putri Ferdianti; Tabhita Sri Hartati Wulandari; Susy Hapsari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
At UPT SD Negeri Kutorejo III Tuban, only 10 of 26 first-grade students (38.46%) had met the Learning Achievement Criteria (KKTP) for recognizing types and nominal values of money, pointing to a learning outcome that remained below the expected standard. To address this, the study set out to describe how the Problem Based Learning (PBL) model was carried out with the support of money- and food-themed flashcards, applied through a mock buying-and-selling activity set up as a small classroom canteen, and to examine the extent to which student learning outcomes subsequently changed. The research followed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, carried out across two cycles that each moved through the stages of planning, acting, observing, and reflecting. A total of 26 first-grade students took part, made up of 12 boys and 14 girls. Data were gathered through achievement tests, classroom observation, and documentation, which were then examined descriptively using a combination of quantitative and qualitative methods. Findings revealed a steady rise in the proportion of students reaching mastery, climbing from 38.46% before the intervention to 69.23% by the end of Cycle I, and reaching 84.62% by the end of Cycle II. These results point to the effectiveness of pairing the Problem Based Learning model with flashcard media in raising first-grade students' Indonesian language outcomes on the topic of recognizing types and nominal values of money.